ACE INHIBITOR ZOFENOPRIL IN COMPLEX THERAPY OF CHRONIC HEART FAILURE AND DILATED CARDIOMYOPATHY - Z. T. Astakhova; D. S. Zagalova (Российский кардиологический журнал)
The study assessed the effectiveness of an ACE inhibitor zofenopril in the treatment of patients with dilated cardiomyopathy (DCMP), complicated by chronic heart failure (CHF). The effects of the medication on clinical status, left ventricular (LV) remodelling, systolic and diastolic function were examined. This six-month study included 35 patients (28 men and 7 women; mean age 49 years). The control group, comparable by age and gender distribution, included 30 healthy people. All patients in the main group received zofenopril (7,5-15 mg/d). Clinical status was evaluated by NYCA Functional Class (FC) of CHF, 6-minute walk test results, and the CHF clinical status assessment scale. The analysed echocardiography parameters reflected LV myocardial remodelling, systolic and diastolic function. In 6 months, zofenopril therapy was linked to improved clinical status, quality of life, and LV systolic function, together with reduced CHF symptoms and LV remodelling. Long-term zofenopril therapy resulted in the reversion of restrictive diastolic dysfunction type into non-restrictive in most patients.